Dietary intake and risk assessment of phototoxic furocoumarins in humans - Schlatter, J.; Zimmerli, B.; Dick, R.; Panizzon, R.; Schlatter, Ch (Food and chemical toxicology, 1991)
The question of whether the furocoumarin content of vegetables is sufficient to induce phototoxic skin reactions after ultraviolet irradiation was examined in two experiments with four human volunteers. In a first experiment, 300 g of celery roots (total phototoxic furocoumarin content 28.2 mug/g) was ingested. No skin reactions were observed after UVA exposure (1.5–9 J/cm 2), and the blood levels of the furocoumarins—psoralen, 8-methoxypsoralen (8-MOP) and 5-methoxypsoralen (5-MOP)—were below the analytical detection limit of 2 ng/ml. To investigate the phototoxic effects of a mixture of the two most important furocoumarins in vegetables, after gastro-intestinal uptake, 8-MOP and 5-MOP (15 mg each) were ingested separately in a 50% alcoholic solution. A strong and persistent erythema was induced in three out of the four subjects (UVA dose: 3–25 J/cm 2). The blood levels immediately before UVA irradiation varied between 14 and 114 ng/ml (8-MOP), and 17 and 70 ng/ml (5-MOP). In the subject who did not show phototoxicity, the blood levels remained at trace levels (3 ng/ml). Two subjects were also tested with a mixture of 10 mg 8-MOP plus 10 mg 5-MOP; in one subject the mixture induced pigmentation only, while in the other a mild-to-medium erythema was induced. The blood levels of the furocoumarins in the two subjects were similar (12–15 ng/ml for 8-MOP and 5-MOP). It is concluded that in humans the phototoxic threshold dose of furocoumarin mixtures is of the order of 10 mg 8-MOP plus 10 mg 5-MOP, which is equivalent to about 15 mg 8-MOP per person (blood levels of 8-MOP and 5-MOP at 30 min after ingestion of about 10–15 ng/ml each). This phototoxic threshold dose was not reached by the consumption of celery roots and other conventional vegetables under normal dietary habits (experimental intake of 2–8 mg per subject of the potentially phototoxic furocoumarin mixture). However, the safety factor between the possible actual intake of furocoumarins and the phototoxic threshold dose is about 2–10, which is relatively small.